The Art of Mesenchymal Stem Cells in Liver Fibrosis Management - Anurogo, Dito; Amansyah, Farid (Bioinformatics and Biomedical Research Journal, 2020)
Liver fibrogenesis is chronic tissue damage characterized by an extracellular accumulation of fibrillar matrix associated with continuous degradation and remodelling. This scientific review describes current concepts on the pathophysiology of liver fibrosis, inflammation as a fundamental concept of liver fibrosis, mechanistic concepts of liver fibrosis, the role of mesenchymal stem cells (MSC) in liver injury, the functional effects of MSC secretome, the advantages of secretome therapy, and the latest research developments on MSC. The role of MSCs has been proven in many liver fibrosis studies involving experimental animals. However, it still requires further research for safety and efficacy aspects